PENERAPAN MODEL PEMBELAJARAN PROJEK BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS 4 SD NEGERI 050726 TANJUNG PURA - Abdul Hafis (Journal of Community Devation, 2025)
This research was conducted with the aim of describing the application of the Project Based Learning Learning Model to Improve Islamic Religious Education Learning Outcomes for Class 4 Students at State Elementary School 050726 Tanjung Pura. This research uses a type of classroom action research (PTK) which aims to improve student learning outcomes by using the project based learning (PjBL) model on Friday prayer material for Friday prayers in class IV elementary school. Data collection techniques in research use test, observation and documentation methods. Data analysis is carried out quantitatively in the form of numbers, then converted into qualitative data in the form of information in the form of sentences. Data was collected through tests distributed to students after implementing the Project Based Learning (PJBL) learning model. The main problem in this research is that there are still students who have not reached the individual completion standard because they obtained scores below the KKM standard. Analysis of the findings of this research will be carried out according to the type of data collected. After the data was analyzed, there were findings in the research, namely that the test results showed that there were 8 students who had not reached the individual completion standard because they got scores below the KKM standard ≥ 75% and 15 students who got scores above or equal to the KKM.